2008
DOI: 10.1080/00207450601067299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Memory Performance, Heart Rate, and Blood Oxygen Saturation Due to 30% Oxygen Administration

Abstract: This study investigated the effect of 30% oxygen administration on memory cognitive performance, blood oxygen saturation, and heart rate. Ten healthy male and female college students (male: 25.8+/-0.8 years, female: 24.2+/-1.9 years) participated in the study. The results of the memory performance analysis reveal that word recall rates were enhanced with 30% oxygen administration compared to 21% oxygen. When 30% oxygen was supplied, blood oxygen saturation was increased and heart rate was decreased compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
29
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 15 publications
12
29
0
2
Order By: Relevance
“…Notably, the task that we used in our study (word list recall) is different in nature from the tasks used in the Jennings et al study and similar in nature to the Wright et al (2005) study. Perhaps on tasks that demand more immediate attentional resources and quicker responses (such as short-term memory tests), older adults are indeed more reliant on their cardiovascular systems to rapidly oxygenate the frontal regions of the brain (Chung and Lim 2008).…”
Section: Age Differences In Hr Responsementioning
confidence: 99%
“…Notably, the task that we used in our study (word list recall) is different in nature from the tasks used in the Jennings et al study and similar in nature to the Wright et al (2005) study. Perhaps on tasks that demand more immediate attentional resources and quicker responses (such as short-term memory tests), older adults are indeed more reliant on their cardiovascular systems to rapidly oxygenate the frontal regions of the brain (Chung and Lim 2008).…”
Section: Age Differences In Hr Responsementioning
confidence: 99%
“…Many studies were performed using various verification methods to describe the effect of highly concentrated oxygen on the cognitive performance of normal healthy people [3][4][5][6][7][8][9][10][11][12][13][14][15]. Highly concentrated oxygen was found to enhance cognitive ability, including visuospatial [7,10], memory [9,[12][13]15], verbal [4], n-back tasks [6], and addition [8].…”
Section: Introductionmentioning
confidence: 99%
“…Highly concentrated oxygen was found to enhance cognitive ability, including visuospatial [7,10], memory [9,[12][13]15], verbal [4], n-back tasks [6], and addition [8]. External oxygen administration improved cognitive performance by decreasing response time [9][10][12][13][14][15] and/or increasing the percentage of correct answers [4,[6][7][8][9][10][12][13]. Many studies also have been undertaken to support the effects of highly concentrated oxygen on cognitive performance of healthy young adults.…”
Section: Introductionmentioning
confidence: 99%
“…15 Studies have shown that patients most prone to harm from diagnostic radiation are children and young adults 16 ; individuals with medical conditions sensitive to radiation, such as diabetes mellitus and hyperthyroidism 17 (which are possible risk factors associated with normal pressure hydrocephalus) 18 ; and individuals receiving multiple doses with time. 19 From the 72 million CT scans performed in the United States during 2007, 1 study estimated that 29,000 future cancers and 14,500 deaths could result from radiation (assuming the cancer incidence to be 0.04%). 20, 21 The radiation doses that an organ receives from a typical CT study involving 2-3 scans are in the range of direct statistical significance for increased cancer risk.…”
Section: Editorialmentioning
confidence: 99%
“…In one study, subjects who inhaled oxygen 60 seconds before attempting to memorize a word list outperformed those who did not. 19 Oxygen cannot be given in advance; it has to be inhaled just before the task, suggesting it is increased blood oxygen saturation that plays a role in memory consolidation. Every time I lecture, I look at my presentation and try to memorize all of its slides so that I can "bridge" them while speaking.…”
mentioning
confidence: 99%